First-Principles Design of Rutile Oxide Heterostructures for Oxygen Evolution Reactions - Lim, Hyeong Yong; Park, Sung O; Kim, Su Hwan; Jung, Gwan Yeong; Kwak, Sang Kyu (Frontiers in Energy Research, 2021)
The oxygen evolution reaction (OER) plays a key role in the determination of overall water-splitting rate. Lowering the high overpotential of the OER of transition metal oxides (TMOs), which are used as conventional OER electrocatalysts, has been the focus of many studies. The OER activity of TMOs can be tuned via the strategic formation of a heterostructure with another TMO substrate. We screened 11 rutile-type TMOs (i.e. MO2; M = V, Cr, Mn, Nb, Ru, Rh, Sn, Ta, Os, Ir, Pt) on a rutile (110) substrate using density functional theory calculations to determine their OER activities. The conventional volcano approach based on simple binding energies of reaction intermediates was implemented; in addition, the electrochemical-step symmetry index was employed to screen heterostructures for use as electrode materials. The results show that RuO2 and IrO2 are the most promising catalyst among all candidates. The scaling results provide insights into the intrinsic properties of the heterostructure as well as materials that can be used to lower the overpotential of the OER.